Reclamation of Dye Coloured of Tenun Textile Wastewater Using Application of Membrane Technology - Siti Norsita, M. R.; Zularisam, A. W.; Nasrullah, M.; Abdul Syukor, Abd Razak; Nur Wahidatul Azura, Zainon Najib (2014)
Homemade textile industry is very famous in the East Coast of Peninsular Malaysia. Known locally as Tenun Diraja Pahang, they are traditionally inherited from generation to generation. The textile industry makes a big contribution to the economic growth due to high demands locally and from abroad. However, this industry produces wastewater which contributes to water pollution since it utilizes a lot of chemicals. The main environmental problem of the textile industry is the high water consumption for their processes. Thus it is very important to reuse textile wastewater. This work is focused on the treatment of a tenun textile wastewater which the water is treated in order to be reused again for several times using combining physicochemical treatment and membrane technology. For the physio-chemical treated of dye wastewater was characterized using jar-tests experiments with PAC, different concentration and pH in order to obtain suitable way to treat the wastewater whether by nanofiltraton (NF) or ultrafiltration (UF). The combination of the physico-chemical treatment and the nanofiltration leads to a COD removal of almost 100%. The results indicate that the NF membrane has satisfactory rejections against various dyes at most testing conditions. As a result, the combination of physicochemical treatment and nanofiltration provided treated water with good enough quality to be reused in the industry.